Effect of curriculum and background factors on students civic development - Abdinasir, Hersi Jama; Al-Hidabi, Dawood Abdulmalek Yahya; Hussien, Suhailah (2020)
Somalia is one of the most fiercely divided countries in the world. The people of Somalia face an identity crisis, as they have more than one identity (clan, national, and religion). In addition to this, the development of good Somali citizens is impeded by the absence of a nation to belong to, as there are clan-based states, a lack of clarity as to whether the nation serves the needs of individual or clans, and an absence of a feeling of obligation towards the nation. These various issues have led to an imperative need to explore as how education as a whole and the curriculum specifically, can build good citizens equipped with a national identity, and a participative attitude. Therefore, the current study investigated whether curriculum can be a panacea for the above mentioned issues. A total of 400 Somali students in their final year of secondary education participated in this study and cross sectional and multiple regression analysis was used. The study found that formal curriculum contributes to the civic development of students and equips them with good citizenship, and a national identity, and hence paves the way for progressive civic participation in the future. In addition, the study revealed that the non-formal part of the curriculum has a statistical significance on the outcomes of national identity and civic participation. The paper also suggested that gender positively develops the student’s national identity and good citizenship, while its effect is lacking on civic participation. The parental education variable was found to have no statistical relationship with any of the dependent variables. Lastly, the study concluded that the combination of four independent variables had a significant impact and could predict civic outcomes.